TINJAUAN FILSAFAT HUKUM TENTANG NUSYUZ (TELAAH PASAL 80 DAN PASAL 84 KOMPILASI HUKUM ISLAM KHI) - Muthahir, Ardi; Fuadi, Ahmad (Law Journal (LAJOUR), 2020)
Divorce is a failure in building a household, Allah really hates this divorce event, but in Islamic teachings it is still permissible, there are many factors that cause divorce, one of which is the existence of nusyuz (durhaka) both nusyuz carried out by wives and husbands. a wife is said to be nusyuz if she does not obey the husband's orders as long as these orders do not contradict the syari'at. Meanwhile, a husband is classified as nusyuz if he does not give his wife's rights properly, because husband and wife are ordinary human beings who at any time can make mistakes and mistakes. However, in the Islamic Law Compilation, there is no confirmation of the rules regarding the husband who performs nusyuz as the wife. In other words, if the husband does Nusyuz there is no legal consequence, based on the above assumptions, it can be concluded that there are various problems related to Nusyuz. This research aims to find out the true nature of nusyuz in KHI. This research is an analytic descriptive study using a normative juridical approach. The collected data were analyzed qualitatively with deductive and inductive thinking methods. In the end it can be concluded that there should be improvements and improvements to the compilation of Islamic law by considering the interests and rights of women in the provisions of the article on nusyuz, because in the compilation of Islamic law there are no articles regulating the problem of husband nusyuz, this tends to be more detrimental to the wife.